2015
DOI: 10.17718/tojde.53012
|View full text |Cite
|
Sign up to set email alerts
|

The Use of 3d Virtual Learning Environments in Training Foreign Language Pre-Service Teachers

Abstract: The recent developments in computer and Internet technologies and in three dimensional modelling necessitates the new approaches and methods in the education field and brings new opportunities to the higher education. The Internet and virtual learning environments have changed the learning opportunities by diversifying the learning options not only in general education but also in the field of foreign language for teachers, curriculum designers and students. Many higher education institutions are employing one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Many studies have confirmed the effectiveness of employing the 3D digital environment in education, including A study by Bedeer (2014) that concluded the effectiveness of using virtual reality technology in developing cognitive achievement, visual thinking, and attitudes towards science among middle school students. A study by Can & Simsek (2015) that confirmed the effectiveness of using a 3D virtual learning environment in training foreign language pre-service teachers at Istanbul University. A study by Bogusevschi, et.…”
Section: Introductionmentioning
confidence: 80%
“…Many studies have confirmed the effectiveness of employing the 3D digital environment in education, including A study by Bedeer (2014) that concluded the effectiveness of using virtual reality technology in developing cognitive achievement, visual thinking, and attitudes towards science among middle school students. A study by Can & Simsek (2015) that confirmed the effectiveness of using a 3D virtual learning environment in training foreign language pre-service teachers at Istanbul University. A study by Bogusevschi, et.…”
Section: Introductionmentioning
confidence: 80%
“…Eleven articles reported that MR technology has been a successful tool to facilitate the process of learning amongst educational institutions [24][25][26][27][28][29][30]. Franciosi [26] states that the use of computer game-based lessons positively impacts vocabulary acquisition, vocabulary learning, vocabulary retention and writing tasks.…”
Section: Facilitating Language Learningmentioning
confidence: 99%
“…Additionally, the increase in usage of such applications is directly correlated to the academic performance of the students (Hanna, Richards, & Jacobson, 2014). The engagement and interest among students tend to be higher when the 3D learning environment is used (Can & Simsek, 2015;Paton & Houghton, 2012) as most students have a presumption that using 3D learning applications the experiences gap from virtual and reality can be significantly reduced (Can et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%